Real-time medium access control in vehicular ad hoc networks - Zhang, Shu (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2013)
The need to reduce the number of fatalities due to road traffic accidents as well as to improve the comfort and efficiency of travel has motivated the vision of vehicular ad hoc networks. Vehicles are envisaged to be able to communicate with each other to avoid imminent danger by exchanging safety messages, which are often safety-critical and time-sensitive. The success or failure of delivering such messages in a reliable and time-bounded manner is the key to the correct operation of safety applications and consequently the well-being of passengers. The unique characteristics of vehicular ad hoc networks, namely high mobility, large and unbounded scale, potentially adverse channel conditions, and the diversity of network density pose huge challenges in achieving real-time communication in these networks. Previous medium access control protocols, whether contention-based or reservation-based, are best-effort, protocols in nature, and cannot provide reliable and guaranteed medium access. A real-time medium access control protocol that can adapt to the fast-changing network topology is required to support the stringent communication requirements of those safety critical applications in vehicular networks.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin.